Analyzing the Role of Higher Education Institutions (Comparing the Independent Campus and Impactful Campus Models from a Theoretical Perspective) - Sulaeman, Sulaeman (Matriks Jurnal Sosial dan Sains, 2025)
This study aims to analyze the fundamental differences between the Kampus Merdeka and Kampus Berdampak models from the perspective of higher education theory. The study was conducted using library research methods through the study of policy documents, journal articles, and relevant theories such as student-centered learning, Mode 2 Knowledge Production, and the Triple Helix. The results of the study indicate that the Kampus Merdeka model emphasizes the flexibility of student learning outside of academic programs to enhance employability, while the Kampus Berdampak model focuses on the tangible contributions of higher education institutions through cross-sectoral collaboration in addressing social, economic, and environmental issues. This study concludes that while the two models have different orientations, they have the potential to complement each other if strategically integrated, thereby supporting the transformation of Indonesian higher education institutions into both academic institutions and centers for sustainable development solutions.